The Effect of Professional Competency, Pedagogic Competencies and Work Disciplines on the Performance of Teachers of Physical Education and Health (PJOK) - Inggar Maizan; Masrun; Damrah; Muhamad Sazeli Rifki (Gladi : Jurnal Ilmu Keolahragaan, 2022)
The problem in this research is the low performance of teachers of Physical Education, Sports and Health (PJOK) in SMP Negeri Se Kota Sungai Penuh. This study aims to determine the effect of Professional Competence, Pedagogic Competence and Work Discipline on the Performance of Physical Education Teachers. The type of research is quantitative using correlation research design with causal associative method. The sample in this study amounted to 28 physical education teachers. Sampling using total sampling technique. Data were collected using measurements of the three variables, namely, using tests for pedagogic and professional variables, and work discipline and teacher performance using existing data. Data were analyzed by path analysis (Path Analysis). Based on the results of data analysis shows that: (1) There is a direct influence between professional competence on the performance of teachers in Physical Education, Sports and Health by 15.8%. (2) There is a direct influence between pedagogic competence on the Performance of Physical Education and Sports Education teachers by 19% (3) There is a direct influence between work discipline on the Performance of Physical Education and Sports Teachers by 19.1%, (4) There is no direct effect between professional competence and pedagogic competence. (5) There is an indirect effect of professional competence on the performance of Physical Education and Health teachers through work discipline of 17.4%, (6) There is no indirect effect of pedagogic competence on the Performance of Physical Education and Health teachers through work discipline.